Revisiting fertility regulation and family ties in Tunisia - Olfa Frini; Christophe Muller (BMC, 2023)
Abstract Background We revisit fertility regulation in Tunisia by examining the role of the extended family. As marriage is the exclusive acknowledged childbearing context, we examine fertility analysis in Tunisia through the sequence: woman's marriage age, post-marriage delay in the first use of contraception, and past and current contraceptive use. We trace the family socio-economic influences that operate through these decisions. Methods Using data from the 2001 PAP-FAM Tunisian survey, we estimate the duration and probability models of these birth control decisions. Results In Tunisia, family ties and socio-cultural environment appear to hamper fertility regulation that operates through the above decisions. This is notably the case for couples whose marriages are arranged by the extended family or who benefit from financial support from both parental families. Conclusion This calls for family planning policies that address more the extended families.